Recent findings and future directions of grafted gum karaya polysaccharides and their various applications: A review. (15th April 2021) - Raj, Vinit; Lee, Jin-Hyung; Shim, Jae-Jin; Lee, Jintae
Highlights: This article reviewed the importance of synthetic modifications of gum karaya. Several approaches used for the extraction of gum karaya are highlighted. Grafting methods for the modification of gum karaya are discussed. Various applications of modified gum karaya in different fields are summarized. This article outlines the future needs for the modification of gum karaya. Abstract: Gum karaya is a polysaccharide that has several industrial applications in the pharmaceutical, food, and environmental fields owing to its hydrophilic, anionic, and biocompatible nature. Gum karaya and its modified forms have been assessed for drug delivery, wastewater treatment, and food industry applications. This review provides a comprehensive overview of various synthetic methods of modification of gum karaya, such as grafting initiated through free radical, microwave-assisted grafting, radiation-assisted, and enzyme-assisted modification methods. In addition, the review outlines collective industrial applications of modified gum karaya in drug delivery systems, removal of heavy atoms, dyes, food, and other biological activities, and suggests possible prospects for gum karaya modification and their remarkable industrial applications.